Ordering Sherpa life through their rituals: Symbolic/Interpretative perspective (A review of "Sherpas through their Rituals" by Sherry B. Ortner) - Dahal, Bishnu Prasad (Occasional Papers in Sociology and Anthropology, 2008)
The PDF of this file is 2,900 kbytes in size and therefore will take a long time to download if you click on the PDF link below. If you would like the file to be sent to you by email, please send a request to info@nepjol.info. Please include the citation below in your request. DOI: 10.3126/opsa.v8i0.1131 Occasional Papers in Sociology and Anthropology Vol.8 2003 p.230-243